Nonmarket action and the International Counter-Money Laundering Act (H.R. 3886) - Feddersen, Timothy James, 1958- (SAGE knowledge. Cases., 2016)
The introduction of H.R. 3886 in 2000 was one in a series of attempts to formalize U.S. banks' monitoring of their customers. The bill was prompted by a government report that named and criticized U.S. banks for laundering billions of dollars linked to drug trafficking, fraud and organized crime. This case describes the international problem of money laundering and summarizes U.S. bank regulations aimed at reducing money laundering activities.